2018
DOI: 10.1097/ajp.0000000000000596
|View full text |Cite
|
Sign up to set email alerts
|

Reorganized Force Control in Elbow Pain Patients During Isometric Wrist Extension

Abstract: The larger change in force direction in pain patients implies redistribution of loads across the arm as an associated effect of pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…In previous studies, no difference was found in force steadiness (SD) during isometric wrist extension between patients with elbow pain and healthy controls [18], whereas force steadiness (CV) has been shown to decrease during experimental muscle pain (hypertonic saline injection) [19]. Contrary, a study investigating discomfort during 96 minutes of sitting on a force platform found that an increase in variability (SD) and a decrease in complexity (SaEn) of the center of pressure signal was associated with increased discomfort [7].…”
Section: Discussionmentioning
confidence: 88%
“…In previous studies, no difference was found in force steadiness (SD) during isometric wrist extension between patients with elbow pain and healthy controls [18], whereas force steadiness (CV) has been shown to decrease during experimental muscle pain (hypertonic saline injection) [19]. Contrary, a study investigating discomfort during 96 minutes of sitting on a force platform found that an increase in variability (SD) and a decrease in complexity (SaEn) of the center of pressure signal was associated with increased discomfort [7].…”
Section: Discussionmentioning
confidence: 88%
“…87,103,184 Interestingly, the distant hyperalgesia is not normalised when patients with osteoarthritis still have pain even after a revision total knee replacement 220 in contrast to the normalisation seen in patients who experience a significant pain reduction after total knee replacement. 87 Spreading hyperalgesia has also been reported in several other conditions, for example, patients with patellofemoral pain, 99,100 LBP, 156,176 neck pain, 42 lateral epicondylalgia, 106,163 and partly in the recovery phase from a tibial fracture. 134 In systemic rheumatologic diseases such as rheumatoid arthritis, pressure pain thresholds are reduced in patients compared with controls, both at the painful joint and occasionally outside.…”
Section: Spreading and Widespread Hyperalgesiamentioning
confidence: 88%
“…1 Hyperalgesia assessed by pressure algometry across painful structures is regularly reported, for example, in patients with painful knee and hip osteoarthritis compared with asymptomatic controls 14,87,103,188 as well as in patients with patellofemoral pain, 99,100 LBP, 156 neck pain, 42 and lateral epicondylalgia. 163,222 Detailed analysis of multiple pressure pain assessment sites around the osteoarthritis knee joint demonstrates that not all sites are equally hyperalgesic and interestingly not clearly correlated to MRI-verified synovitis. 188 After intraarticular injection of analgesia and steroid into the osteoarthritic knee, the peripatellar pressure hyperalgesia was reduced.…”
Section: Localised Hyperalgesiamentioning
confidence: 99%
“…Similarly, a different study reported differences in the co-activation of muscles during an isometric endurance task, displaying a reduced activity of the ECR at the end of the contraction (Alizadehkhaiyat et al, 2007b). In addition, Mista et al (2018) in concluded that there is a reorganization of force control strategies in chronic LE patients based on the analysis of isometric contractions. On the other hand, previous studies had evidenced a higher fatigability of the ECR in LE during isometric contractions (Rojas et al, 2007).…”
Section: Discussionmentioning
confidence: 99%